NATIVE NICKEL IN THE TAG HYDROTHERMAL FIELD SEDIMENTS (MID-ATLANTIC RIDGE, 26°N): SPACE TROTTER, GUEST FROM MANTLE, OR A WIDESPREAD MINERAL, CONNECTED WITH SERPENTINIZATION? - Dekov V. (My University, 2006)
Tiny metallic particles have been found in the sediments of the Trans-Atlantic Geotraverse (TAG) hydrothermal field, Mid-Atlantic Ridge (MAR). The metallic grains are almost pure Ni and have compositional and structural characteristics similar to those of other terrestrial metallic Ni0 occurrences. Native nickel grains, documented here for the first time in oceanic sediments, appear in calcareous oozes intercalated with metalliferous layers, layers with bedrock rubble, and sporadically scattered cosmic microspherules. There are three possibilities for the metallic Ni0 genesis: (1) cosmic, (2) lower mantle at the core-mantle boundary, or (3) upper mantle/lower crust. The flake-like appearance of the Ni0 grains rules out cosmic ablation origin. No unequivocal evidence was found that the Ni0 particles could have formed under high-pressure conditions similar to those at the core-mantle boundary. Ni0 formation through seawater serpentinization of the upper mantle/lower crust is the most plausible mechanism. At the slow spreading MAR, seawater penetrates down through highly fractured crest zone and serpentinizes the olivine and pyroxene of the upper mantle/lower crust ultramafics/mafics. Serpentinization results in the generation of highly reduced volatile species: H2 and hydrocarbons. In such an extremely reduced environment, Fe and other transition metals (Co, Ni, Cu, Zn) released from olivines and pyroxenes tend to appear as native metals if fS2 approaches 0. The lightened serpentinized blocks uplift and expose the serpentinized ultramafics/mafics at the rift valley's walls. I speculate that tectonic movements and weathering could liberate the native metallic grains scattered in the serpentinized rocks, which may then have been dispersed in the proximate sediments by near-bottom currents. Copyright 2006 by the American Geophysical Union.